The influence of small hydroelectric power plants on the richness and composition of Odonata species in the Brazilian Savanna. Issue 1 (2nd January 2018) - Klein, C.E.; Pinto, N.S.; Spigoloni, Z.A.V.; Bergamini, F.M.; de Melo, F.R.; De Marco J., P.; Juen, L.
Abstract : Regardless of the economic and social development that damming processes related to hydroelectric power plants bring to a region, they represent a wide range of disturbances to the physical, chemical, and biological characteristics of rivers. We evaluated the effects of dams on Odonata communities from the southeastern region of Goiás, Brazil. Thirteen streams connected to three dams were studied: seven were used as reference samples (located upstream from the damming site, therefore not directly affected by damming) and six were used as affected area samples (located downstream from the dam). A total of 1128 odonates from six families, 22 genera, and 39 species were captured and identified. The results showed that Odonata richness was affected by the presence of dams, with different effects on Anisoptera and Zygoptera suborders. We discuss that these effects are related mostly to the physical and chemical variables in waterbodies directly affected by small hydroelectric power plants (SHPs). It is possible that negative effects on the Odonata community in SHP areas are related to changes in waterflow, pH and turbidity.